Insulin Resistance and Its Association with Metabolic Syndrome in Korean Children. (31st December 2017) - Cho, Jinkyung; Hong, Haeryun; Park, Soohyun; Kim, Shinuk; Kang, Hyunsik
Abstract : Background . This study investigated the association between insulin resistance (IR) and metabolic syndrome (MetS) in children. Methods . A cross-sectional study involving 1036 healthy children aged between 7 and 13 years was conducted. Homeostasis model assessment of insulin resistance (HOMA-IR) was calculated as an index of IR. Participants were classified according to the HOMA-IR quartiles. Results . Incremental, linear trends were found in age (p < 0.001 ), body mass index (BMI) (p < 0.001 ), body fat (p < 0.001 ), waist circumference (p < 0.001 ), resting blood pressures (BP) (p < 0.001 ), triglycerides (TG) (p < 0.001 ), total cholesterol (TC) (p < 0.001 ), high density lipoprotein-cholesterol (HDL-C) (p < 0.001 ), FBG (p < 0.001 ), and insulin (<0.001) according to incremental HOMA-IR categories (from the 1st to 4th quartile). Compared with children in the 1st HOMA-IR quartile, children in the 4th HOMA-IR quartile had significantly higher odd ratios (ORs) of abnormalities in systolic (p = 0.051 ) and diastolic BP (p = 0.005 ), FBG (p < 0.001 ), TG (p < 0.001 ), TC (p = 0.016 ), and HDL-C (p = 0.006 ) even after adjustments for age, gender, BMI, and body fat percentage. Children in the 3rd HOMA-IR quartile had significant abnormalities in FBG (p < 0.001 ), TG (p = 0.001 ), and HDL-C (p = 0.010 ) even after adjustments for the covariates. Conclusion . The current findings suggest that IR is significantly associated with the clustering of MetS risk factors in children in Korea.